FACTORS AFFECTING SERVICE DELIVERY IN PARASTATALS: A CASE STUDY OF RURAL ELECTRIFICATION AUTHORITY, KENYA - BARONGO, MORAA RIZIKI (KABARAK UNIVERSITY, 2018)
There is need for critical service delivery in REA a state corporation which is mandated to accelerate the pace of rural electrification in order to promote sustainable socioeconomic development. Like any other organizations ,it faces complains about service delivery, it is normal for a human being not to get satisfaction no matter how good a service but organizations will always try and go overboard to please their customers. It is also important to observe that there are notable successes, failures and missed opportunities in the history of State Corporations in Kenya. Financial sector regulators represent notable successes in the service delivery sector, clearly facilitating the positioning of Kenya as a financial, transport and communications hub in the continent and the world at large. In all these cases government entities which were not working optimally were either transformed through engagement with strategic and/or anchor investors, or introduction of missing links in the product value chains, which then added value before these could be partially privatized. The purpose of this study was to investigate the factors affecting service delivery in parastatals in Kenya a Case of Rural Electrification Authority. The objectives were; to find out how organization structure affects service delivery, to find out how communication affects service delivery, to identify how knowledge and skills affect service delivery, to identify service delivery principles and policies in parastatals. To achieve this objective the Researcher employed descriptive research design and made use of questionnaires to collect data from the respondents. The target population of the study was 13 customer service staff working at rural electrification authority and 97 major suppliers. The collected data was coded and entered into SPSS for analysis. Using SPSS (statistical package for social sciences.) Data was grouped into frequency distribution tables to indicate variable values and number of occurrences in terms of frequency. Parastatals will benefit from the findings of this study as they will use the results of the study to improve service delivery. It will be of help to the government in formulating policies that will guide the operations of the state owned corporations to ensure good service delivery, the customers who are the citizens will be able to know the service delivery principles and what to expect when being served. Researchers and scholars will benefit from the study, as they will use the findings of the study as a source of information.
FULL TEXT
Keywords: Organization structure, Communication, knowledge and skills, service delivery principles.